Significantly alleviated PM2.5 pollution in cold seasons in the Beijing-Tianjin-Hebei and surrounding area: Insights from regional observation - Yangxi Chu; Xiyuan Chi; Jinhong Du; Jingchun Duan; Chak K. Chan; Lu, Keding; Lina Yin; Jihua Tan; Jingnan Hu; Fahe Chai (Atmospheric Research, 2024)
PM2.5 pollution has been greatly alleviated in the Beijing-Tianjin-Hebei (BTH) and surrounding area since the implementation of Action Plans for blue skies. Regional air pollution covering multiple cities has recently become common, but an overview from a regional perspective is scarse. In this work, based on PM2.5 chemical composition data collected in “2 + 26” cities during four consecutive autumn-winter seasons (AWS, from October to next March) from October 2016 to March 2020, we determined the main components driving the increase in PM2.5 mass concentration within different PM2.5 concentration regimes. Regionally, in the low PM2.5 regime (daily concentration ≤ 75 μg/m3), the PM2.5 mass remained organic matter (OM)-driven during the four AWSs. In the high PM2.5 regime (daily concentration > 75 μg/m3), regional PM2.5 increase pattern rapidly transformed from OM-driven during the 2016–2017 AWS to secondary inorganics-driven during the latter three AWSs, with nitrate becoming the dominant component, driving PM2.5 increase in almost 90% cities in the region. These transitions not only reflect the effectiveness of policies to control emissions from coal combustion and biomass burning in recent years, but also highlight the need to further reduce nitrogen oxides emissions from diesel vehicles, non-road mobile machinery and industry. Besides, the control of sulfur dioxide and primary organic matter should not be neglected, given the substantial contribution of PM2.5 sulfate under stagnant and humid meteorological conditions, especially in the geographically central and southern parts of the region, and the need for in-depth air quality improvement if the PM2.5 concentration standards are tightened. Considering the dominance of nitrate in driving regional PM2.5 pollution, more research on nitrate formation and its atmospheric and climatic impacts is warranted.
Keywords: ammonium nitrate; PM chemical composition; Primary organic aerosol; Regional air pollution; Secondary aerosol